Acute cholecystitis in elderly patients after hip fracture: Incidence and epidemiology. Issue 3 (21st March 2015) - Choo, Suk Kyu; Park, Hyung Jun; Oh, Hyoung‐Keun; Kang, Yoo Kyung; Kim, Youngwoo
Abstract : Aim: Acute cholecystitis is a medical complication that can develop in the postoperative period after hip surgery. However, few studies have examined this complication in elderly patients. Our aim was therefore to evaluate the incidence and clinical manifestations of acute cholecystitis after hip fracture in elderly patients. Methods: Medical records and radiological studies of patients aged older than 65 years who underwent hip surgery for femoral neck or intertrochanteric fractures at a single hospital from April 2003 to March 2013 were reviewed retrospectively. We analyzed the type of cholecystitis (acalculous or calculous), clinical manifestations, fracture type (neck or trochanteric fracture), age, sex, body mass index, type of surgery, time to surgery, time from surgery to onset of acute cholecystitis and the timing of ambulation in acute cholecystitis cases. Results: There were nine confirmed acute cholecystitis cases among 1211 hip fractures; thus, the incidence of acute cholecystitis within 2 months after hip fracture surgery was 0.74%. Conclusions: The incidence of acute cholecystitis was higher than we expected, and this condition can lead to more serious problems if overlooked. Acute cholecystitis as a medical complication after hip fracture was underestimated in previous studies. Furthermore, acute cholecystitis should be considered as a complication of hip fracture, not hip surgery, in the elderly. The present study does not imply that hip fracture causes acute cholecystitis, although elderly hip fracture patients are in an extremely debilitated state and are prone to developing acute cholecystitis.Geriatr Gerontol Int 2015; ●●: ●●–●●.